Variasi Temperatur Pencampuran Terhadap Parameter Marshall pada Campuran Lapis Aspal Beton - Raya S, Sarkis Enda; Pratomo, Priyo; Herianto, Dwi (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2015)
This study was conducted to determine the effect of temperature variations on the mixing processof the asphalt concrete AC-WC (Asphalt Concrete-Wearing Course) subtle gradations in themiddle limit and lower limit of the Marshall parameters with reference to specifications of BinaMarga, 2010.From the results of experiments conducted that the optimum asphalt content is used to middle limitusing a asphalt content of 5,7% and 6,8% for the lower limit after that mixing was done usingtemperature variation of 120 o C, 130 o C, 140 o C, 150 o C, and 160 o C.To a mixture of Laston AC-WC subtle gradations middle limit grading 5,7% asphalt contentmixing temperature using a temperature of 120 o C, 130 o C, 140 o C, 150 o C, 160 o C and still meet allstandards of marshall parameters. Ideal mixing temperature variations in the middle limit ofmixing temperature 150 o C-160 o C. While the lower limit to the level of 6,8% asphalt contentmixing temperatures between 120 o C-160 o C did not meet the specifications, because the MQ valuebelow the minimum value of 250 kg / mm.Keywords: Mixing temperature, 2010 Specification, Marshall, Asphalt Concrete-Wearing Course(AC-WC) Subtle Gradation.